Zytokine im psychoneuroendokrin-immunologischen Kontext unspezifischer muskuloskeletaler Schmerzen - Ahrens, Carsten; Schiltenwolf, Marcus; Wang, Haili (Der Schmerz, 2012)
Cytokines are coordinators of immune homeostasis. Evidence for the participation of cytokines in neurogenic inflammation, peripheral and central sensitization and hyperalgesia as well as for induction of inflammatory immune responses by pain-related catastrophizing is well documented. A disproportion of proinflammatory and anti-inflammatory cytokines is known to be a contributory cause of pain and pain behavior. Embedded into psychoneuroendocrine immunological feedback control systems cytokines are able to perpetuate a virtuous circle between local inflammation and systemic pain behavior (pain/sickness behavior) thus contributing to chronification of nonspecific musculoskeletal pain.In this model avoidance and pain-related nonrecognition as key components of systemic pain behavior lead to maintenance of the virtuous circle by generating of a local inflammation with local and systemic consequences. This model can explain the success of established therapy concepts from the point of view of psychoneuroimmunology, such as fear avoidance, which are effectively used as principal components in multimodal pain therapy.
Gesehen am 03.04.2018